Direct and Highly Selective Conversion of Synthesis Gas into Lower Olefins: Design of a Bifunctional Catalyst Combining Methanol Synthesis and Carbon–Carbon Coupling. (9th March 2016) - Cheng, Kang; Gu, Bang; Liu, Xiaoliang; Kang, Jincan; Zhang, Qinghong; Wang, Ye
Abstract: The direct synthesis of lower (C2 to C4 ) olefins, key building‐block chemicals, from syngas (H2 /CO), which can be derived from various nonpetroleum carbon resources, is highly attractive, but the selectivity for lower olefins is low because of the limitation of the Anderson–Schulz–Flory distribution. We report that the coupling of methanol‐synthesis and methanol‐to‐olefins reactions with a bifunctional catalyst can realize the direct conversion of syngas to lower olefins with exceptionally high selectivity. We demonstrate that the choice of two active components and the integration manner of the components are crucial to lower olefin selectivity. The combination of a Zr–Zn binary oxide, which alone shows higher selectivity for methanol and dimethyl ether even at 673 K, and SAPO‐34 with decreased acidity offers around 70 % selectivity for C2 –C4 olefins at about 10 % CO conversion. The micro‐ to nanoscale proximity of the components favors the lower olefin selectivity. Abstract : Kombinierte Katalyse : Über einem difunktionellen Katalysator, der ein Zr‐Zn‐Oxid für die Methanolsynthese mit SAPO‐34 für die selektive C‐C‐Kupplung kombiniert, wird Synthesegas bei 673 K mit 74 % Selektivität in C2 ‐ bis C4 ‐Olefine umgewandelt. Die Kontrolle des Hydriervermögens der beiden Komponenten spielt dabei eine entscheidende Rolle.